2021
DOI: 10.1007/s11661-021-06363-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ausforming on the Macro- and Micro-texture of Bainitic Microstructures

Abstract: The reason why variant selection phenomena occur in ausforming treatments is still not known. For that reason, in this work, the effect of compressive deformation on the macro and micro-texture of a bainitic microstructure was analyzed in a medium-carbon high-silicon steel subjected to ausforming treatments, where deformation was applied at 520 °C, 400 °C and 300 °C. The as-received material presented a very weak $$\left\langle {3\, 3\, 1} \right\rangle$$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Then, Tdef was held for 15 s before samples were compressed up to 10 % at 0.04 s -1 . In previous works in this same steel and with the same austenitization and deformation conditions, it was shown that, although some stress/strain induced bainite/martensite formed during this deformation step [25], the presence of these phases did not alter the trends observed in terms of variant selection with respect to samples in which no strain induced transformations were detected [19] and, thus, their presence could be neglected. After the stress was removed, samples were held at Tdef for 10 s and cooled down to 300 °C, temperature which was held for 1 h before cooling down to room temperature.…”
Section: Methodsmentioning
confidence: 69%
See 4 more Smart Citations
“…Then, Tdef was held for 15 s before samples were compressed up to 10 % at 0.04 s -1 . In previous works in this same steel and with the same austenitization and deformation conditions, it was shown that, although some stress/strain induced bainite/martensite formed during this deformation step [25], the presence of these phases did not alter the trends observed in terms of variant selection with respect to samples in which no strain induced transformations were detected [19] and, thus, their presence could be neglected. After the stress was removed, samples were held at Tdef for 10 s and cooled down to 300 °C, temperature which was held for 1 h before cooling down to room temperature.…”
Section: Methodsmentioning
confidence: 69%
“…A step size of 0.35 μm was utilized and only the ferrite (bcc) structure was considered. The XRD data and the EBSD data had also been used in two previous works [19,22] in which through characterizations was performed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations